Dying in the margins: Experiences of dying at home for people living with financial hardship and deprivation - Naomi Richards; Sam Quinn; Emma Carduff; Merryn Gott (Elsevier, 2024)
Home dying is a policy indicator of 'quality dying' in many high-income countries, but there is evidence that people living in areas of higher deprivation have a reduced likelihood of dying at home. However, there is limited research which centres the views and experiences of people living with both socioeconomic deprivation and serious advanced illness. We deployed visual methods to address this gap in knowledge, focusing on barriers to, and experiences of, home dying for people experiencing poverty and deprivation in the UK. We used photovoice and professional documentary photography between April 2021 and March 2023 with eight participants with serious advanced illness, six of whom had died by the end of the study. We also worked with four bereaved family members to create digital stories. This produced a large volume of multi-modal data which we analysed using a thematic, iterative, interpretive approach. Key findings included the high costs of dying at home, the nature and impact of which were conveyed by images such as a heating thermostat set to low. Images also expressed how for some participants, the environment inside and outside the home was experienced as oppressive and alienating because of cramped, materially poor social housing, as well as urban noise, crime, mould and damp, and a lack of access to outside space. Nevertheless, the home environment was important to all participants, particularly as a site to support the continuation of their identity and autonomy, and some were explicit about wanting to remain at home for as long as possible. This study provides unique insights regarding the significant policy shift needed to improve the extent and experience of home dying for the growing number of people dying in the context of financial hardship and deprivation both in the UK, and elsewhere.